THE TREATMENT OF UNAMORTIZED DISCOUNT AND EXPENSE APPLICABLE TO BONDS REFUNDED BEFORE MATURITY. - Lemke, B. C. (The Accounting Review, 1947)
Abstract The substantial fall in interest rates which began in the early 1930s resulted in a widespread exercise by corporations of the option to call bonds before maturity, where such provision had been incorporated in the bond terms. Even though a call premium had to be paid, the resulting saving in interest cost often was sufficient to make bond refunding appear mandatory. Other reasons which might have tipped the scales in situations where the interest saving may not have been significant, were the substantial saving in taxes based on income in a high tax year if a relatively large amount of unamortized bond discount and expense, applicable to the refunded bond, was present, and secondly, the opportunity to issue refunding bonds which omitted restrictive covenants found in the old bonds. The true nature of unamortized bond discount or bond premium and the correct presentation of the bond liability can be inferred from the ordinary compound interest computations used to arrive at the present worth of bonds.